(untitled) (Medico Legal Update, 2021)
Background: Urinary urgency incontinence is characterized by symptoms of involuntary loss of urine that preceded or accompanied by sudden desire to void. Fecal incontinence is defined as involuntary passage of stool through the anus. It may vary from soiling to complete evacuation. This involuntary loss of feces, flatus or urge incontinence adversely affects quality of life. Objectives: To evaluate the efficacy and safety of sacral neuromodulation on these pathologies. Method: Following a detailed investigation, 21 patients with either urinary incontinence, or both urinary and fecal, who did not respond to medical and behavioral treatment were offered the sacral neuromodulation therapy and followed for at least 12 months post implant regarding response and development of complication if any found. Results: In the period from November 2015 to May 2017. The unit of neurogenic bladder and neuromodulation in surgical subspecialty hospital, medical city complex had implanted 21 Patients with urinary incontinence were using from (4-17) pads/day (mean of 10.5/day) presacral neuromodulation which were declined significantly to (0-3) pads/day (mean of 2.2/day). From the eighteen patients who presented with fecal incontinence after the implantation of sacral neuromodulation interstim 11 permanent devices only four remained incontinent .and from the nine patients who presented with erectile dysfunction only two remained impotent. Conclusion: The use of Sacral Neuromodulation in Iraqi patients with Urinary and Fecal Incontinence is safe and effective